1988
DOI: 10.1002/fut.3990080107
|View full text |Cite
|
Sign up to set email alerts
|

Risk and return in cattle and hog futures

Abstract: onsiderable controversy exists over the amount of risk in futures markets.C Keynes (1930, p. 137; see Peck 1983, p. 68) believed that futures prices are quite variable and thus price risk is associated with the ownership of futures contracts. He believed that risk premiums are paid by hedgers to speculators for bearing risk.' Keynes estimated the risk premiums to be sizable-that is, on the order of 10 to 20% per annum.A different approach to examining risk is provided by the capital asset pricing model (CAPM).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

1990
1990
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Nevertheless, it is fair to say that, if there do exist candidates that seem to fit the backwardation mold, the livestock commodities are the prime ones. The finding of significantly positive returns is fairly consistent over a number of different subperiods.23 Others have noted the persistent tendency for livestock futures to be downward biased estimates of eventual spot prices.24 In this context it is interesting to note that Breeden ( 1 980) found significantly positive consumption betas for futures in this category; as did Carter et al (1983) and Elam and Vaught (1988) using a standard CAPM framework with the market proxied by a weighted average of the S&P 500 and the Dow Jones Commodity Index.25 There are some theories about why these commodities may be different. For example, Koppenhaver (1 983) notes that "one possible explanation of the risk premiums.…”
Section: Are Real Price Trends Responsible?mentioning
confidence: 77%
“…Nevertheless, it is fair to say that, if there do exist candidates that seem to fit the backwardation mold, the livestock commodities are the prime ones. The finding of significantly positive returns is fairly consistent over a number of different subperiods.23 Others have noted the persistent tendency for livestock futures to be downward biased estimates of eventual spot prices.24 In this context it is interesting to note that Breeden ( 1 980) found significantly positive consumption betas for futures in this category; as did Carter et al (1983) and Elam and Vaught (1988) using a standard CAPM framework with the market proxied by a weighted average of the S&P 500 and the Dow Jones Commodity Index.25 There are some theories about why these commodities may be different. For example, Koppenhaver (1 983) notes that "one possible explanation of the risk premiums.…”
Section: Are Real Price Trends Responsible?mentioning
confidence: 77%
“…These authors found that from 1998 to 2004, the hog futures market was an unbiased predictor of cash prices. Elam and Vaught [ 10 ] also discussed the risks and benefits of hog futures. These studies all show that the hog futures market must actively cultivate hedgers, guide the appropriate speculators and crack down on excessive speculators, thereby preventing excessive speculation, which leads to market instability.…”
Section: Introductionmentioning
confidence: 99%
“…3Again there are difficulties in interpreting the alpha values as excess returns given zero investment but this too has become standard practice. 4The main studies of commodity futures in addition to that by Dusak (1973) are Carter, Rausser, and Schmitz (1983); Baxter, Conine, and Tamarkin (1985); So (1987); Elam and Vaught (1988);…”
Section: The Capital Asset Pricing Model and Futures Tradingmentioning
confidence: 99%
“…In addition, Breeden (1980) applies a different version of the CAPM, using the consumption beta model. 'See Dusak (1973); Carter, Rausser, and Schmitz (1983); Marcus (1984); Baxter, Conine, and Tamarkin (1985); and Elam and Vaught (1988). 6The CAPM provides no insight into what the appropriate interval for analysis should be.…”
Section: The Capital Asset Pricing Model and Futures Tradingmentioning
confidence: 99%